2020
DOI: 10.1002/jmv.26604
|View full text |Cite
|
Sign up to set email alerts
|

Screening and pharmacodynamic evaluation of the antirespiratory syncytial virus activity of steroidal pyridine compounds in vitro and in vivo

Abstract: Respiratory syncytial virus (RSV) causes serious lower respiratory tract infections and there are currently no safer or more effective drugs available. It is important to find novel medications for RSV infection. A series of steroidal pyridines were synthesized for screening and evaluation of their antiviral activity and investigation of their antiviral mechanism of action. Compound 3l had the highest antiviral activity, with a half‐maximal effective concentration (EC50) of 3.13 μM. Compound 3l was explored fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
(60 reference statements)
0
6
0
Order By: Relevance
“…149 In 2020, Wang et al reported on a series of 17-pregnenolone cyanopyridine derivatives as anti-RSV agents. 152 The best compound 62 (Figure 19) exhibited an EC 50 of 3.13 μM by CPE on HEp-2 cells infected with RSV Long strain (VR-26) coupled with a CC 50 of 538.65 μM. Investigations of the MoA highlighted that 62 had antiviral activity at a postentry stage and downregulated TLR-3, IL-6, and RIG-I expression, which was confirmed in vivo.…”
Section: ■ Inhibitiors Of the Replication Complexmentioning
confidence: 90%
See 2 more Smart Citations
“…149 In 2020, Wang et al reported on a series of 17-pregnenolone cyanopyridine derivatives as anti-RSV agents. 152 The best compound 62 (Figure 19) exhibited an EC 50 of 3.13 μM by CPE on HEp-2 cells infected with RSV Long strain (VR-26) coupled with a CC 50 of 538.65 μM. Investigations of the MoA highlighted that 62 had antiviral activity at a postentry stage and downregulated TLR-3, IL-6, and RIG-I expression, which was confirmed in vivo.…”
Section: ■ Inhibitiors Of the Replication Complexmentioning
confidence: 90%
“…In 2020, Wang et al reported on a series of 17-pregnenolone cyanopyridine derivatives as anti-RSV agents . The best compound 62 (Figure ) exhibited an EC 50 of 3.13 μM by CPE on HEp-2 cells infected with RSV Long strain (VR-26) coupled with a CC 50 of 538.65 μM.…”
Section: Host-targeting Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al 76 reported the synthesis of 17-pregnenolone cyanopyridines 113a–l through a simple procedure in moderate-to-good yields. First, pregnenolone reacted with acetic anhydride under catalyzed conditions to give the acetylated product 112 .…”
Section: Synthesis Of Binary Systemsmentioning
confidence: 99%
“…Wang et al 76 reported the evaluation of pyridinyl steroids 113a-l (Fig. 4) as antiviral agents against respiratory syncytial virus (RSV).…”
Section: Antiviral Activitymentioning
confidence: 99%